2018
DOI: 10.14738/assrj.53.3704
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Mental Well-Being of Undergraduate Students in Karachi

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Thus, it can be concluded that sociodemographic factors are not associated with the mental well-being of the respondents living in the Jakarta Greater Area. This can happen because individuals' well-being can be influenced by many factors aside from sociodemographic factors, namely demographic factors (Ryff, 1989), personality (Ryan & Deci, 2001), social support (Shujaat, 2018) as well as contextual and situational factors (van Hoorn, 2008). The results show that almost half of the respondents who filled out the questionnaire admitted that they only left their homes 1-2 times a week (45.9%) (table 4).…”
Section: Mental Well-being From Sociodemographic Statusmentioning
confidence: 99%
“…Thus, it can be concluded that sociodemographic factors are not associated with the mental well-being of the respondents living in the Jakarta Greater Area. This can happen because individuals' well-being can be influenced by many factors aside from sociodemographic factors, namely demographic factors (Ryff, 1989), personality (Ryan & Deci, 2001), social support (Shujaat, 2018) as well as contextual and situational factors (van Hoorn, 2008). The results show that almost half of the respondents who filled out the questionnaire admitted that they only left their homes 1-2 times a week (45.9%) (table 4).…”
Section: Mental Well-being From Sociodemographic Statusmentioning
confidence: 99%